WORK ETHIC AND TECHNICAL SKILL IMPROVE EMPLOYEE PERFORMANCE - Rudi Santoso (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to produce a generalization of a phenomenon found during the research process by collecting various kinds of library source material. The variables used in this study are education, discipline (work ethic), and work (technical) ability to drive employee performance. This study uses a qualitative descriptive method with a literature study approach. The basic postulate (basic assumption) in this study is that higher education/training (as a hard skill competency) and discipline (as a soft skill competency) play a role in improving employee performance. This basic postulate or basic assumption is based on an empirical study of past research. The results of the study show the same symptoms where the level of education, discipline (work ethic as a manifestation of soft skills), and technical abilities (hard skills) can drive employee performance improvement.